2019
DOI: 10.3389/fmech.2019.00039
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interfacial Water and Applied Potential on Friction at Au(111) Surfaces

Abstract: The tribological properties between an AFM tip and a Au(111) surface in an aqueous environment is influenced by an applied electrical potential. Using lateral force microscopy, we measure the resulting friction force, while simultaneously applying a predetermined electrical potential on the Au surface via a three-electrode setup. Applying a positive potential to the Au surface forms an interfacial water layer at the Au/electrolyte interface, which sharply increases friction. However, when an anodic potential i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 48 publications
(62 reference statements)
2
14
0
Order By: Relevance
“…Correspondingly, in situ control of friction 2 , 3 , adaptive friction change 4 and superlubricity 5 7 were identified as the greatest challenges in tribology. Switchable or controllable friction is thereby recognized as an increasingly significant and important topic 8 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, in situ control of friction 2 , 3 , adaptive friction change 4 and superlubricity 5 7 were identified as the greatest challenges in tribology. Switchable or controllable friction is thereby recognized as an increasingly significant and important topic 8 11 .…”
Section: Introductionmentioning
confidence: 99%
“…For the GE surfaces with different electric charges, the ions and water molecules between the interfaces would have different structures. According to previous studies, when a gold surface has the appropriate positive potential, water molecules adsorb on the GE to form an ordered ice-like water layer with viscosities 10 5 –10 7 times that of bulk water (Figure a,b). , The ordered water layer exposes a large number of dangling hydroxyl groups, which are capable of hydrogen bonding with polar hydrophilic probes ,,, (panel 1 of Figure c). However, at positive potentials, the Cl – adsorption is inevitable, which would inhibit the formation of ice-like water. , In this experiment, the maximum potential used, V app = +0.6 V, and the amount of adsorbed Cl – was insufficient to disrupt the ice-like water structure, similar to the findings of previous studies. ,, In contrast, when the GE potential was negative, the ordered water structure was disrupted and ice-like water did not form. ,, Due to electrostatic attraction, the hydrated cations were adsorbed on the interface water layer at the GE (Figure ).…”
Section: Results and Discussionmentioning
confidence: 82%
“…Gold-coated mica was used as the working electrode (Figure ). A NaCl solution of 0.1 M concentration was used as the electrolyte because the Debye length was less than 1 nm at this concentration, which indicated that the double-layer force could be neglected. ,, In this electrochemical system, the electrochemical potential of the gold surface is maintained between −0.6 and +0.6 V because in this potential range, no Faraday process, such as the oxidation of the GE, occurs. , All electrochemical potentials were recorded relative to the quasi-reference electrode of the Ag wire. The potential point of zero charge ( U pzc ) in the electrochemical system is approximately 100 mV …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7). This scenario is supported by the fact that water layers are known to form ice like structures near metal surfaces and reorient with the strength and directly of applied external fields [50]. 6 Example 2…”
Section: Resultsmentioning
confidence: 98%